Alpha-Synuclein Induced Immune Cells Activation and Associated Therapy in Parkinson’s Disease - Su, Ruichen; Zhou, Tian (Frontiers in Aging Neuroscience, 2021)
Parkinson's disease (PD) is a neurodegenerative disorder closely related to immunity. One of the most critical parts is the interaction between α-synuclein and immune cells. Current studies have demonstrated that the accumulation of α-synuclein could induce the autoimmune response and then deteriorate PD progression. This review discusses the mechanism of interaction between α-synuclein and the immune system. During PD development, abnormally accumulated α-synuclein becomes an autoimmune antigen and binds to Toll-like Receptors (TLRs) to activate microglia. These microglia will differentiate to microglia type 1 (M1) subtype, activating intracellular inflammatory pathways, releasing pro-inflammatory cytokines, or promoting CD4+ T cells differentiation to pro-inflammatory Th1 and Th17 subtypes. Given the central role of α-synuclein in PD immune system, the potential immune-therapeutic target related to α-synuclein is important. An enhanced understanding of the immunity-associated mechanism of PD and promising immune-therapeutic strategies is expected to be established.